Exercise, Nrf2 and Antioxidant Signaling in Cardiac Aging - Narasimhan, Madhusudhanan; Rajasekaran, Namakkal S. (Frontiers in Physiology, 2016)
Aging is represented by a progressive decline in cellular functions. The age-related deformities in cardiac behaviors are the loss of cardiac myocytes through apoptosis or programmed cell death. Oxidative stress (OS) and its deleterious consequence contribute to age-related mechanical remodeling, reduced regenerative capacity, and apoptosis in cardiac tissue. The pathogenesis of OS in the elderly can predispose the heart to other cardiac complications such as atherosclerosis, hypertension, ischemic heart disease, cardiac myopathy, and so on. At the molecular level, oxidant-induced activation of Nrf2 (Nuclear erythroid-2-p45-related factor-2), a transcription factor, regulates several genes containing AREs (Antioxidant Response Element) and bring the respective translates to counteract the reactive radicals and establish homeostasis. Myriad of Nrf2 gene knockout studies in various organs such as lung, liver, kidney, brain, etc. have shown that dysregulation of Nrf2 severely affects the oxidant/ROS sensitivity and predispose the system to several pathological changes with aberrant cellular lesions. On the other hand, its gain of function chemical interventions exhibited oxidant stress resistance and cytoprotection. However, thus far, only a few investigations have shown the potential role of Nrf2 and its non-pharmacological induction in cardiac aging. Therefore, here we review the involvement of Nrf2 signaling along with its responses and ramifications on the cascade of OS under acute exercise stress (AES), moderate exercise training (MET), and endurance exercise stress (EES) conditions in the aging heart.